2011
DOI: 10.1103/physrevc.83.044315
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy structure of the even-ARu96104isotopes viaet al.

Abstract: The transient field perturbed angular correlation technique has been used with Coulomb excitation in inverse kinematics to perform a systematic measurement of the g factors of the first excited 2 + 1 states in the stable even-A isotopes 96−104 Ru. The measurements have been made relative to one another under matched kinematic conditions and include the first measurement of the g(2 + 1 ) = +0.47(3) in 96 Ru.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…However, aside from noting that there may be grounds to increase the previously reported g factors of the neutron-rich isotopes [6,7] by about 20%, these values are reported without adjustment in Table IX. Finally, it is to be noted that Taylor et al [25] performed transient-field g-factor measurements on the Ru isotopes in parallel with the present work. Their adopted g factors agree within the experimental uncertainties • .…”
Section: Adopted G Factorsmentioning
confidence: 80%
See 2 more Smart Citations
“…However, aside from noting that there may be grounds to increase the previously reported g factors of the neutron-rich isotopes [6,7] by about 20%, these values are reported without adjustment in Table IX. Finally, it is to be noted that Taylor et al [25] performed transient-field g-factor measurements on the Ru isotopes in parallel with the present work. Their adopted g factors agree within the experimental uncertainties • .…”
Section: Adopted G Factorsmentioning
confidence: 80%
“…[15]. It was found that extreme values must be assumed for the magnitude of g(4 (25). Combining these values with the precessions for these isotopes in Table II determines that the absolute g factors in Table II are given by g = ∆Θ/φ(∞) = ∆Θ/(−50.34 ± 3.08), where ∆Θ is in mrad.…”
Section: Isotopesmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial and final energies of the 100 Pd ions, entering and leaving the gadolinium foil, were estimated to be 213. in Ref. [34].…”
Section: Calculation Of Gmentioning
confidence: 98%
“…Especially, the determined hard-core values are not reliable since missing data on larger distances and the large errors do not allow a reasonable determination of these values. With the recently measured g factor for the 2 + 1 state of g = 0.47(3) [44] (another recently measured value is g(2 + 1 ) = 0.41(3) [45], one can calculate the parameters describing the hyperfine interaction strength in the Ru isotopes using Eq. (6) to C 2 = 3.3 ± 0.8 ps and C 4 = 1.5 ± 0.5 ps.…”
Section: Deorientation Effectmentioning
confidence: 99%